Akuntansi Prospektif Untuk Memenuhi Kebutuhan Pemakaian Tentang Informasi Keuangan Masa Depan Dan Tantangan Bagi Profesi Akuntan - Lili Arnita (Journal of Accounting and Investment, 2001)
Writing is the idea originated from the limitations of conventional financial statements which have the nature of historical cost and simply describe the financial events of the past. With the development needs of users of financial information to predict the financial future will require some information about the company's forecasts or projections will come. Such financial information may be used by the user to guide the decision making favorable economic.